Terrorism formation with supranational character: kosmopolitization factor - V. I. Dolgy (MGIMO University Press, 2013)
The article indicates the general trends leading to the transformation of contemporary terrorism from national to transnational stage, above all the global role of the cosmopolitization. It contains a collative analyses of the two types of terrorism. One of them, existing at the age of industrial modernity, and another one corresponds to the contemporary societies.